Power rating of photovoltaic modules repeatability of measurements and validation of translation procedures - Paghasian, Karen (ProQuest LLC, 2010)
Power rating photovoltaic modules at six irradiance and four temperature matrix levels of IEC 61853-1 draft standard is one of the most important requirements to accurately predict energy production of photovoltaic modules at different climatic conditions. Two studies were carried out in this investigation: a measurement repeatability study and a translation procedure validation study. The repeatability study was carried out to define a testing methodology that allows generating repeatable power rating results under outdoor conditions. The validation study was carried out to validate the accuracy of the four translation procedures: the first three procedures are from the IEC 60891 standard and the fourth procedure is reported by NREL. These translation procedures are needed to translate the measured data from the actual test conditions to the reporting rating conditions required by the IEC 61853-1 draft standard. All the measurements were carried out outdoors on clear days using a manual, 2-axis tracker, located in Mesa/Tempe, Arizona. Four module technologies were investigated: crystalline silicon, amorphous silicon, cadmium telluride, and copper indium gallium selenide. The modules were cooled and then allowed to naturally warm up to obtain current-voltage data at different temperatures. Several black mesh screens with a wide range of transmittance were used for varying irradiance levels. From the measurements repeatability study, it was determined that: (i) a certain minimum distance (2 inches) should be maintained between module surface and the screen surface; (ii) the reference cell should be kept outside the screen (calibrated screen) as opposed to inside the screen (uncalibrated screen); and (iii) the air mass should not exceed 2.5. From the translation procedure validation study, it was determined that the accuracy of the translation procedure depends on the irradiance and temperature range of translation. The difference between measured and translated power at maximum power point (Pmax) is determined to be less than 3% for all the technologies, all the irradiance/ temperature ranges investigated and all the procedures except procedure 2 of IEC 60891 standard. For the procedure 2, the difference was found to fall between 3% and 17% depending on the irradiance range used for the translation. The difference of 17% is very large and unacceptable. This work recommends reinvestigating the cause for this large difference for procedure 2. Finally, a complete power rating matrix for each of the four module technologies has been successfully generated as per IEC 61853-1 draft standard.--Abstract.